Pengaruh Laba Akuntansi, Opini Audit, Solvabilitas dan Ukuran Perusahaaan Terhdap Audit Delay Pada Perusahaaan Manufaktur Sektor Pangan yng Terdaftar Di Bursa Efek Indonesia Pada Tahun 2020-2022 - napitupulu, samuel (Akuntansi Prima, 2025)
This research aims to analyze the factors that influence audit delays in food sector manufacturing companies listed on the Indonesia Stock Exchange in the 2020-2022 period. The factors studied include accounting profit, audit opinion, solvency, and company size. The research method used is quantitative using secondary data from related articles and journals. Partial test results show that accounting profit, solvency and company size do not have a significant influence on audit delay, while audit opinion has a significant influence on audit delay. Meanwhile, simultaneously accounting profit, audit opinion, solvency and company size have a significant effect on audit delay. Keywords: audit delay, accounting profit, audit opinion, solvency, company size